ANALISIS PENARIKAN HUTANG DALAM KAITNNYA DENGAN RENTABILITAS PADA PT. TUNAS BROTHERS DI BANDAR LAMPUNG - Gunawan Gunawan (Universitas Bunda Mulia, 2017)
This study aims to determine how the effects of the use of capital (derived from debt and own capital) is used by companies of the rate of return on equity. Is the policy for the withdrawal of debt has just run in the sense of providing a beneficial effect for the owners of the company. Hypothesis os : if the level of rate of return of the acquired company is greater than the amount the interest rate, then the withdrawal will have a positive debt to rate of return on equity. Analysis is done using quantitative analysis for the purpose of comparingthe theory that become the guidelines applied by the company’s application and the rentability analysis and quantitative analysis tools with ration analysis. Profit margin, operating Turnover assets, rate of return and rate of return on equity. From the results of research conducted was even its own capital rentability of the company acquired during the year under study shows a growing trend (5.35%, 6.78%, 11.68%, 8.66%) but the actual level of rtaae of return of own capital it can be achieved even greater (ie could reach 7.01%, 9.78%, 12.43%, 11.44%) if only the company during the year no interest loan. Key Words- Debt, equity, rate of return.